Universal Music DJ sampler 4. - Universal Music (Malaysia). (Petaling Jaya, Selangor : Universal Music, 1999)
Contains eighteen songs from pop R&B, rock alternative, dance, original soundtracks and dance genre.
CD 1 : You've Got A Way / Shania Twain -- Tell Me It's Real / K-ci & Jojo -- Summer Son / Texas -- Where My Girls At / 702 -- All That I Can Say / Mary J. Blige -- Promises / Def Leppard -- Animal Instinct / The Cranberries -- All Star / Smash Mouth -- Beat Mama / Cast -- The Bigger I Laugh, The Harder I Cry / Spin Doctors -- Gravel On The Ground / Amigone -- Viva La Radio-Almighty remix / Lolly -- Give It To You-95 South remix / Jordan Knight -- Body / Funky Green Dogs -- When You Say Nothing At All / Ronan Keating (Boyzone) -- Save It For Later / Harvey Danger -- Bailamos / Enrique Iglesias -- Standing Together / George Benson.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English